Climate change, human health, and the exposome: Utilizing OMIC technologies to navigate an era of uncertainty - Hana Abdelzaher; Sherouk M. Tawfik; Ahmed Nour; Sarah Abdelkader; Shaimaa Tarek Elbalkiny; Mohamed Abdelkader; Walaa A. Abbas; Anwar Abdelnaser (Frontiers Media S.A., 2022)
Climate change is an anthropogenic phenomenon that is alarming scientists and non-scientists alike. The emission of greenhouse gases is causing the temperature of the earth to rise and this increase is accompanied by a multitude of climate change-induced environmental exposures with potential health impacts. Tracking human exposure has been a major research interest of scientists worldwide. This has led to the development of exposome studies that examine internal and external individual exposures over their lifetime and correlate them to health. The monitoring of health has also benefited from significant technological advances in the field of "omics" technologies that analyze physiological changes on the nucleic acid, protein, and metabolism levels, among others. In this review, we discuss various climate change-induced environmental exposures and their potential health implications. We also highlight the potential integration of the technological advancements in the fields of exposome tracking, climate monitoring, and omics technologies shedding light on important questions that need to be answered.